Answer:
-12/5 - 2
Step-by-step explanation:
-18÷3×8(-8)/-5×-2+(-2) =
-6×8(-8)/-5×-2+(-2) =
-48(-8)/-5×-2+(-2) =
6/-5×-2+(-2) =
-12/5 - 2
Sorry it's quite complex, simplify then... had to use an nspire
1. x=1.22248
2. x=15624.8
3. x=0.057522 (shown in picture)
4. x=-0.732487
too bad i cant upload more than 1 pic
Answer:
4/3
Step-by-step explanation:
i took the quiz hehe
The vertex form is
Step-by-step explanation:
The given equation is a parabola. The vertex of the parabola is of the form
The parameters of the parabola are and
The vertex of the x-coordinate is given by
Thus, substituting the values of a and b in , we get,
Now, substituting in , we get,
Thus, the vertex is
The equation of parabola to be in vertex form is
where a is the coefficient of , h is vertex of the x-coordinate and k is the vertex of the y-coordinate.
Hence, and
Thus, substituting the values in the equation of the vertex form,
Hence, the vertex form is